Genetically modified bacteria for targeted phototherapy of tumor - Deng, Xiangyu (2022)
Live attenuated bacteria have been used as target vehicles for genetic therapy of malignant carcinoma because they can be reprogrammed by following simple genetic rules and have the ability to target tumor hypoxic region. In this research, noninvasive Escherichia coli (E. Coli) is genetically modified through the plasmid transfection to afford E. Coli(p) with overexpressed human catalase for catalyzing H2O2 into O2 in the tumor site. The produced O2 is consequently converted to cytotoxic 1O2 under near-infrared (NIR) light irradiation for photodynamic therapy. Chlorin e6 (Ce6) is chosen as the photosensitizer for its excellent photodynamic ability, and polydopamine (pDA) is employed to encapsulate Ce6 for its good biosafety, photothermal ability, and adhesion capacity with bacteria. Dopamine polymerizes in the presence of Ce6 to form pDA/Ce6, and then E. Coli(p) is coated with pDA/Ce6 to afford the final E. Coli(p)/pDA/Ce6. The obtained system is intravenously administrated for selective accumulation and replication in the hypoxic tumor. NIR light irradiation is introduced to enable photothermal and O2-enhanced photodynamic therapy. On account of complementary combination, the system exhibits efficient antitumor effect in vitro and in vivo. Thus, the integration of genetically modified bacteria with pDA/Ce6 presents a promising application potential for precise tumor inhibition.